Intencionalidades e influências das avaliações em larga escala no trabalho de docentes de duas escolas da rede municipal de Uberlândia - MG - Ferreira, Lívia Andrade (2018)
This dissertation investigates the influence of large-scale evaluations on the work of teachers from two schools in the city of Uberlândia - MG, based on the perception of the agents involved in the teaching and learning process, specifically teachers, supervisors and inspectors. Through the analysis of the changes in the Brazilian historical and political context that led to the restructuring of education and teaching work, the understanding of how large-scale evaluations have influenced this work and the verification of the vision of education professionals about external evaluations, we seek to understand the extent to which large-scale evaluations interfere in the pedagogical practice and provoke the devaluation of these professionals as subjects who think and organize their own practice. Considering the assumption that external evaluations can affect the teaching performance, we seek to elucidate how current evaluation systems have been used by the State as regulators of pedagogical practices and the consequences of this use in the accountability of teachers and schools, aggravated by the lack of consideration of the different contexts in which school institutions meet. Through a qualitative approach, we performed a theoretical-empirical study, supported by bibliographic reviews, documentary analysis and semi-structured interviews. The research revealed discrepant positions of the education professionals both in relation to the appropriation of the evaluation data and in relation to the repercussion of these in the emotional and professional aspects of the teacher, which is associated to the context of the institutions in which they work. In addition, it has shown that the current structure and form of data processing resulting from external evaluations have negatively reflected the teaching work, often provoking curricular narrowing, training, pedagogical engaging, uncritical practices and segregation of students, which indicates the need for reflection on the purposes to which large-scale evaluations have served.